(untitled) (Research, Society and Development, 2022)
Digital radiology has several advantages over conventional radiology, from image acquisition to image storage, and has been widely used. Thus, the present work configures a retrospective and quantitative study with the objective of counting the number of radiographic exams performed and presenting the benefits of this technology for the undergraduate course. The number of digital radiographs performed in the period of one year in the dentistry course at Centro Universitário Newton Paiva located in the city of Belo Horizonte, MG was considered in the study. For this, the database of the institution’s digital radiology laboratory was used, which is composed of intraoral and extraoral digital radiographic exams. This laboratory runs an extension project for undergraduate students in dentistry, in which the members help in carrying out the exams. In the period of 1 year, 8,928 digital radiological images were performed. It can be concluded, then, that the teaching of digital radiology in university centers is of great importance for students, since digital radiology has great benefits for the patient and for the professional or student who performs it, in addition to presenting a considerable demand.